'A most miserable hotchpotch': Charles Bean and the origins of the First World War film collection. Issue 2 (3rd May 2016) - Eisenberg, Daniel
ABSTRACT: The story of the moving picture collection of the First World War held by the Australian War Memorial is a frustrating, complex and intriguing one. Charles Bean struggled from the earliest days of the war to get Australian film, shot by Australian cinematographers, into Australian hands – with limited success. Using the 1919 report Charles Bean wrote on his dealings with the War Office Cinematograph Committee (WOCC) as a framing device, this paper traces some of the paths taken by the earliest of these fragile records. By using three films as case studies, exploring the history of the WOCC and its major players and drawing on (and pulling apart) contemporary correspondence, diaries and notes a chaotic picture emerges. Though Bean himself is not without sin in the mishandling of the Australian footage, his fight for these first few films highlights the constant tension between film as a content-driven commodity and film as an archival object.